2021
DOI: 10.1186/s12879-021-05803-7
|View full text |Cite
|
Sign up to set email alerts
|

Population-based HIV prevalence, stigma and HIV risk among trans women in Nepal

Abstract: Background Transgender women (trans women) in Nepal are underserved in the HIV response. Data are needed to determine the HIV prevalence disaggregated from other key populations and to identify the particular risks faced by this community. Trans women are marginalized around the world and research is also needed to determine the impact of stigma on HIV risk to inform trans-specific interventions. Methods In 2019, we conducted the first population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
(32 reference statements)
0
5
0
6
Order By: Relevance
“…Em todo o mundo mulheres trans experimentam formas cruzadas de discriminação devido a suas posições sociais marginalizadas, estruturalmente produzidas nas intersecções de cor, etnia, cidadania, gênero, sexualidade, idade, deficiência e classe [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . O Brasil lidera o ranking mundial de assassinatos de pessoas trans, com um assassinato a cada 48 horas 7 , tornando esta evidência ainda mais preocupante no cenário brasileiro.…”
Section: Discussão Categoria 1: Interseccionalidade: a Tipificação Da...unclassified
See 1 more Smart Citation
“…Em todo o mundo mulheres trans experimentam formas cruzadas de discriminação devido a suas posições sociais marginalizadas, estruturalmente produzidas nas intersecções de cor, etnia, cidadania, gênero, sexualidade, idade, deficiência e classe [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . O Brasil lidera o ranking mundial de assassinatos de pessoas trans, com um assassinato a cada 48 horas 7 , tornando esta evidência ainda mais preocupante no cenário brasileiro.…”
Section: Discussão Categoria 1: Interseccionalidade: a Tipificação Da...unclassified
“…Todas as categorias de violência foram mais altas para a população de pessoas trans. Estimativas mostram que mulheres trans negras e latinas representam quase a totalidade de todas as vítimas de homicídio transgênero nos Estados Unidos, onde estas também são assediadas regularmente até pela polícia 17,20 .…”
Section: Discussão Categoria 1: Interseccionalidade: a Tipificação Da...unclassified
“…Condom use is still below (61-73%) an optimal level in key populations like female sex workers, men who have sex with men, and transgender who received educational interventions (Deuba et al, 2020;National Centre for AIDS and STD Control [NCASC], 2018). In addition, there is a greater prevalence of condomless receptive anal intercourse among male sex with male and transgender people (Wilson et al, 2021). A study by Kakchapati et al (2018) revealed that only about 29% of FSWs had knowledge about HIV and it was not associated with safe sexual practices.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kakchapati et al (2018) revealed that only about 29% of FSWs had knowledge about HIV and it was not associated with safe sexual practices. Some recent studies (Shrestha et al, 2017;Kakchapati et al, 2018;NCASC, 2018;Deuba et al, 2020;Wilson et al, 2021) have indicatedthat despite the decades of targeted interventions including IEC activities against HIV and AIDS in Nepal, risk behaviors of key populations have not changed as expected and trend of the concentrated epidemic has not declined satisfactorily. This alarming situation demands research to explore the major means and modes of communication through which key populationsfrequently use to get and share HIV and AIDS-related information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation